ANALISIS PENGARUH BIAYA PRODUKSI DAN TINGKAT PENJUALAN TERHADAP LABA KOTOR - MUKHLISHOTUL JANNAH (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2018)
The cost of production required by the company will continue to increase fromyear to year. One reason is the increase in raw material prices used, thiscondition encourages the amount of revenues a company experiencingchanges. Similarly, PT Indocement Tunggal Perkasa Tbk, production costscontinue to increase. This condition can be seen in the change in gross profit,from 2004 to 2013 corporate profits have increased and decreased.The purpose of this research is to know the effect of Production Cost and Saleslevel to Gross Profit. The type of research used is causal associative research.The samples used are saturated samples. The type of data used is primary andsecondary data. Data analysis technique used is multiple regression.